Figurative Language, Emotion and Ideology in U.S. and Russian Geopolitical Narratives Towards Africa - (:unkn) unknown (My University, 2024)
This corpus-based study focuses on the revival of the geopolitical struggle in Africa between the U.S. and Russia (Stronski, 2019; Cohen, 2020). I investigate a corpus of speeches given by the Russian Foreign Minister Sergey Lavrov and the U.S. Secretary of State Anthony Blinken during their respective visits to Africa in July and August 2022. On the one hand, I examine to what extent the two antagonists combine figurative language with various discursive and psycho-cognitive strategies in order to sustain and convey their ideological standpoint and their geopolitical agenda in Africa. On the other hand, I analyze how they select and construe some particular lexical units and structures, literally or figuratively, for the sake of foregrounding or backgrounding events, participants, and the relationships between them. Finally, based on a sample of reactions to the narratives, section (2.5) deals with their socio-cognitive perceptions by the African leaders and people.
Keywords: African Research